2014
DOI: 10.1021/cm500720x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [(SnSe)1.16–1.09]1[(NbxMo1–x)Se2]1 Ferecrystal Alloys

Abstract: Modification of the modulated elemental reactant method allowed the first reported synthesis of quaternary [(MX) z ] m [(T x T′1–x )­X2] n compounds with controlled compositions. Metastable ferecrystal compounds, [(SnSe)1.16–1.09]1[(Nb x Mo1–x )­Se2]1 with x = 0, 0.26, 0.49, 0.83, and 1, were synthesized and characterized by X-ray diffraction, electron probe microanalysis (EPMA), and scanning transmission electron microscopy (STEM). Misfit layer dichalcogenide analogues, showing controlled alloying of the dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…In this study, we present an in-depth account of the high temperature thermoelectric properties of (SnSe) 1.16 NbSe 2 or Sn 1.16 NbSe 3.16 mist selenide. This compound has been studied by a few authors in the past for various aspects, such as, (1) its complex crystal structure 27 which ensures low lattice thermal conductive like all other mist layered chalcogenides, (2) synthesis and study of ferecrystalline alloys/thin lms [28][29][30] which have shown that charge transfer and hence the electronic properties in this mist are tunable and, (3) polycrystalline room temperature electronic properties 16,27 which indicate its low room temperature electrical resistivity ($6 mU m). These previous studies make this mist selenium compound a suitable candidate for thermoelectric investigation as well.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we present an in-depth account of the high temperature thermoelectric properties of (SnSe) 1.16 NbSe 2 or Sn 1.16 NbSe 3.16 mist selenide. This compound has been studied by a few authors in the past for various aspects, such as, (1) its complex crystal structure 27 which ensures low lattice thermal conductive like all other mist layered chalcogenides, (2) synthesis and study of ferecrystalline alloys/thin lms [28][29][30] which have shown that charge transfer and hence the electronic properties in this mist are tunable and, (3) polycrystalline room temperature electronic properties 16,27 which indicate its low room temperature electrical resistivity ($6 mU m). These previous studies make this mist selenium compound a suitable candidate for thermoelectric investigation as well.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of each block can be individually controlled as well as the order of the layers, resulting in over 20,000 distinct nanoarchitectures for n and m less than 10. [36] The three constituents can also be combined into one heterostructure, either by alloying the constituents that have a common structure [37], to form a random (A,B)C alloy, or by preparing three component heterostructures with distinct layers of each constituent forming an ordered ABAC alloy. These two possibilities provide access to a large number of new compounds, many more than one would like to make, so the challenge is to understand how properties change as the constituent thicknesses, order, and composition are varied to accelerate the search for the optimum properties for a particular application.…”
Section: Modulated Elemental Reactantsmentioning
confidence: 99%
“…[37] The composition control is accomplished via calibrations similar to what was discussed earlier. There are at least two different approaches based on the number of sources used.…”
Section: Preparing Random Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[19][20][21] Still, many experimental efforts failed because the small grains also reduced the power factor S 2 /r. in misfit-layered materials [26][27][28][29][30][31][32] or materials with crystallographic shear (CS) planes. 22 Therefore, materials containing inherent phonon scattering centers at the atomic level have attracted scientific attention recently.…”
Section: Introductionmentioning
confidence: 99%